An efficient technique for primer development and application that integrates fluorescent labeling and multiplex PCR1. (1st October 2013) - Culley, Theresa M.; Stamper, Trevor I.; Stokes, Richard L.; Brzyski, Jessica R.; Hardiman, Nicole A.; Klooster, Matthew R.; Merritt, Benjamin J.
Abstract : Premise of the study: Development of genetic markers can be costly and time‐consuming, especially when multiple primer pairs are fluorescently labeled. This step was streamlined by combining two techniques in the same PCR reaction: (1) custom‐labeling of primers by the investigator and (2) multiplexing multiple primers together in the same reaction. Methods and Results: This technique was successfully used to develop microsatellite markers in several plant species. Microsatellites amplified with this multiplexing process were identical to those generated from PCR using individual primer pairs and with traditional methods using a priori labeled fluorescent primers. Tests of PCR cycling programs revealed that conditions recommended for the commercial kit generated stronger fragment peaks than the previously recommended cycling protocol. Conclusions: This technique is an efficient and economical way to fluorescently label multiple microsatellite primers in the same reaction. It is also applicable to other markers used in PCR amplification of genetic material.